(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article highlights the interrelationships and differences between comparative linguistics, contrastive linguistics, and translation studies, as well as their significance in linguistic research and applied translation. The article examines the history of the formation of these three fields, their main theoretical directions, and their role in modern linguistics. In particular, the role of comparative and contrastive linguistics in linguistic analysis, the theoretical and practical aspects of translation studies are widely analyzed.